PROSODI PANTUN DALAM ACARA PERNIKAHAN ADAT MELAYU PONTIANAK - Simatupang, Heru Darmawan; Syahrani, Agus; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The Pontianak Malay community has a culture that is still maintained, namely the procession between goods in the Pontianak Malay traditional wedding. In this case, the research focuses on rhyme speech in Pontianak Malay traditional marriages through acoustic phonetic studies. The problem in this study includes aspects of frequency and duration of rhyme speech in Pontianak Malay traditional marriages. This study uses a quantitative descriptive method and uses an acoustic phonetic study approach as an analytical study tool. The source of the data in this study was taken from the video recording of the marriage between Reza Okta Indriyandi, S.Kom and Emmy Rustianty, S.Sos. Data retrieval using documentation techniques with data collection tools, namely voice recorders, laptops, gadgets, and stationery. This research succeeded in getting 17 rhymes with a total of 68 target sentences. The final result of the data processing of this research is presented into tables and figures using the praat application as a data analysis tool. The data were analyzed based on their acoustic characteristics, namely frequency and duration. This research is expected to be documented so that it contributes to linguistic literature in phonology, especially regional languages.